2020
DOI: 10.1016/j.janxdis.2020.102289
|View full text |Cite
|
Sign up to set email alerts
|

Fear and avoidance of healthcare workers: An important, under-recognized form of stigmatization during the COVID-19 pandemic

Abstract: Highlights Little is known about healthcare worker stigmatization (HCWS) during COVID-19. HCWS involves fear and avoidance of healthcare workers, for fear of infection. Our research indicates that HCWS is a widespread, under-recognized problem. HCWS is associated with the COVID Stress Syndrome. Interventions that reduce the COVID Stress Syndrome may reduce HCWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
228
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(278 citation statements)
references
References 16 publications
(25 reference statements)
17
228
0
10
Order By: Relevance
“…In an online study of 3551 non-health care workers in the USA and Canada, high percentage of Canadians and Americans believed that healthcare workers should not be allowed to go out in public, should have restrictions on their freedoms, should be isolated from community and should be separated from their families. 10 Little has been done politically to recommend that healthcare workers be protected for carrying out their duties. 10 The absence of protections—and indeed that bullying often arises from authorities—creates anxiety for health workers in that they subsequently confront bullying and stigmatising situations alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an online study of 3551 non-health care workers in the USA and Canada, high percentage of Canadians and Americans believed that healthcare workers should not be allowed to go out in public, should have restrictions on their freedoms, should be isolated from community and should be separated from their families. 10 Little has been done politically to recommend that healthcare workers be protected for carrying out their duties. 10 The absence of protections—and indeed that bullying often arises from authorities—creates anxiety for health workers in that they subsequently confront bullying and stigmatising situations alone.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Little has been done politically to recommend that healthcare workers be protected for carrying out their duties. 10 The absence of protections—and indeed that bullying often arises from authorities—creates anxiety for health workers in that they subsequently confront bullying and stigmatising situations alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps surprisingly, large proportions of US and Canadian adults report wanting to avoid HCWs (47%), believing that HCWs should be isolated from their own families (31%), and believing that HCWs should not go out in public (25%). [31] The willingness to restrict the freedoms of HCWs and desire for social distance can be expected to greatly reduce the emotional support available to HCWs outside of work.…”
Section: Mental Health Concerns Of Front-line Hcws During the Pandemicmentioning
confidence: 99%
“…Groups such as health workers and medics have been unable, due to their professional responsibilities, to maintain the prescribed social distance from others, and have been exposed to significant levels of discrimination, even though they work under very difficult conditions for the well-being of the public at large, while facing increased personal risk. Although they have been widely praised as heroes, they have also been stigmatized, avoided, and excluded due to their being perceived as sources of infection (Taylor et al, 2020;World Health Organization, 2020d), which was also similarly observed during previous outbreaks such as SARS (Bai et al, 2004).…”
Section: Introductionmentioning
confidence: 96%